Program, nauczanie i weryfikacja wiedzy z przedmiotu zastosowania matematyki w finansach i bankowości - Chrzan, Piotr (Curriculum, Education and Knowledge Validation on Math Application in Finance and Banking, 2006)
Modem finance is embedded in mathematic, econometric and information sciences methods. The Chief Committee of Higher Education (CCHE) resolute to adjoin subject called "Math application in finance and banking" to standard majors (core courses) for uniform undergraduate master's studies as well as for Bachelors Studies.Accurate, chronic and consistent adaptation of CCHE projected program throughout thirty teaching hours is very difficult primarily due to the necessity of introducing many subject matters not included in the talked about program. Achieving proper accuracy, permanence and consistency is particularly important owing to the first time option for finance and banking students to be introduced to math application subject. The teaching thought forms common students outlook of the quantity methods function in finance and banking. This viewpoint can encourage to or discourage students from further study of quantitative methods and their applications.This paper covers authors' experience relating to implementation and knowledge confirmation of subject called "Math applications in finance and banking" taught at full time and part time like (weekend) studies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 17-25